Intraorbital Wooden Foreign Body with Intracranial Extension : A Case Report - Amanda N Shinta; Purjanto Tepo Utomo; Agus Supartoto (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2018)
Purpose : The aim of this study is to report a case of intraorbital wooden foreign body with intracranial extension to the frontal lobe and its management. Method : This is a descriptive study: A 53 year-old male referred due to wooden stick stucked in the orbital cavity causing protruding eyeball and vital sign instability. Result : Right eye examination revealed light perception visual acuity, with bad light projection and bad color perception, inwardly folded upper eyelid, proptosis, conjunctival chemosis, corneal erosion and edema, dilated pupil with sluggish pupillary light reflex and limited ocular movement in all direction. Vital sign was unstable with decreasing blood pressure, increasing temperature and heart rate. CT Scan showed complete fracture of the orbital roof due to penetration of the wooden stick, pneumoencephalus, cerebral edema and hematoma. Emergency craniotomy was performed to remove the penetrating wooden stick and bone segment in the frontal lobe and fracture repair. Ophthalmologist pulled the remaining stick, released the superior rectus muscle and repaired the lacerated eyelid. Outcome visual acuity was no light perception with lagophthalmos and limited ocular motility. Patient was admitted to Intensive Care Unit one day post-operatively and treated with systemic and topical antibiotic. Conclusion : Any case presenting with intraorbital foreign body must undergo immediate neuroimaging to exclude any intracranial extension, especially in patients with worsening general condition.